High-frequency oscillations in awake patients undergoing brain tumor-related epilepsy surgery. (27th March 2018) - Feyissa, Anteneh M.; Worrell, Gregory A.; Tatum, William O.; Mahato, Deependra; Brinkmann, Benjamin H.; Rosenfeld, Steven S.; ReFaey, Karim; Bechtle, Perry S.; Quinones-Hinojosa, Alfredo
Abstract : Objective: To examine the relationship between high-frequency oscillations (HFOs) and the presence of preoperative seizures, World Health Organization tumor grade, and isocitrate dehydrogenase 1 (IDH1) mutational status in gliomas. Methods: We retrospectively studied intraoperative electrocorticography recorded in 16 patients with brain tumor (12 presenting with seizures) who underwent awake craniotomy and surgical resection between September 2016 and June 2017. The number and distribution of HFOs were determined and quantified visually and with an automated HFO detector. Results: Five patients had low-grade (1 with grade I and 4 with grade II) and 11 had high-grade (6 with grade III and 5 with grade IV) brain tumors. An IDH1 mutation was found in 6 patients. Patients with a history of preoperative seizures were more likely to have HFOs than those without preoperative seizures (9 of 12 vs 0 of 4, p = 0.02). The rate of HFOs was higher in patients with IDH1 mutant (mean 7.2 per minute) than IDH wild-type (mean 2.3 per minute) genotype ( p = 0.03). Conclusions: HFOs are common in brain tumor-related epilepsy, and HFO rate may be a useful measure of epileptogenicity in gliomas. Our findings further support the notion that IDH1 mutant genotype is more epileptogenic than IDH1 wild-type genotype gliomas.